Pendampingan pembuatan Sistem Biopori dalam menanggulangi masalah limbah rumah tangga Desa Tebaban - Mijahamuddin Alwi; Musabihatul Kudsiah; Arif Rahman Hakim; Saprudin Jauhari; Baiq Fitri Rahmawati (Universitas Hamzanwadi, 2021)
Making Biopore holes is not difficult and does not require special skills but the results and benefits are much greater. Biopore functions as a water catchment and processing household waste. This method is quite effective in a densely populated environment and limited land. The purpose of this service is to provide knowledge and its application on how to process organic household waste through the Biopore system. The problems faced in Tebaban Barat village are sorting, separating, handling, and managing household waste. Handling household waste is only carried out by transporting waste from the house to the house, then throwing it into the landfills. So that the existing household waste is only wrapped in plastic and waiting for the schedule to pick up the landfills every week, this situation causes a bad smell. Implementing this activity includes field surveys, communication, collaboration, socialization, and mentoring. The survey results obtained are communicated with the village and residents. Then an agreement was made regarding the manufacture of Biopore holes. Furthermore, socialization about waste and conducting assistance activities for making Biopore holes was carried out. The results of the community assistance activities in making Biopore holes, 90% of the residents who attended were able to practice directly making Biopore holes either manually or using a drill and how to fill holes and harvest Biopore results. After the mentoring, the results of the visit carried out by the Team, 70% of the residents have implemented it in their respective homes even though it is still made manually. The activity invites interest from some people because it is seen from the usefulness of this activity. The Biopore is very suitable to be applied in that environment.